Systematic review and pooled analysis of survival rates, success, and outcomes of osseointegrated implants in a variety of composite free flaps. Issue 9 (13th May 2020) - Khadembaschi, Darius; Brierly, Gary I.; Chatfield, Mark D.; Beech, Nicholas; Batstone, Martin D.
Abstract: The aim of this review was to provide an update on survival rates of osseointegrated implants into common composite free flaps used for maxillary and mandibular reconstructions and identify factors affecting outcomes. PubMed, Medline, Embase, and Cochrane databases were searched. Included studies reported implant survival by flap type. Results were pooled and survival was estimated with the Kaplan‐Meier method. Variables affecting survival were assessed using Cox regression. Thirty‐two of the 2631 articles retrieved were included, totaling 2626 implants placed into fibula, iliac crest, scapula, and radial forearm free flaps. Pooled survival showed 94% 5‐year survival of implants in fibula and iliac crest with no difference between groups ( P = .3). Factors effecting survival included radiotherapy (HR 2.3, 95% CI 1.2‐4.6, P = .027) and malignant disease (HR 2.2, 95%CI 1.6‐3.1, P  < .001). Implant survival appears adequate across common flap types; however, there are limited numbers reported in less common flaps.